Computed tomography enterography or magnetic resonance enterography in Crohn's disease - which to choose? - Azevedo,Aida (2019)
ABSTRACT Rationale and objectives: Evaluation of Crohn's disease by computed tomography enterography, magnetic resonance imaging enterography and colonoscopy is essential for disease monitoring. The aim of this study is to evaluate this exams acuity. Materials and methods: Patients with histological diagnosis of Crohn's disease who underwent computed tomography enterography, magnetic resonance imaging enterography and colonoscopy in the period of January 1st, 2009 and July 31st, 2016 and the realization of these exams did not exceed a time interval of 6 months was included. Sensitivity, specificity, positive and negative predictive values (PPV, NPV), Cohen's kappa (K), agreement and disagreement were calculated. Results: Comparing computed tomography enterography and magnetic resonance imaging enterography with colonoscopy, there was an agreement of 85.7% and a disagreement of 14.3% in Crohn's disease overall detection, for both exams. Computed tomography enterography and colonoscopy showed greater agreement in abscesses and lumen reduction detection (C = 95.2%) and magnetic resonance imaging enterography and colonoscopy in abscesses detection (C = 92.9%). Comparing magnetic resonance imaging enterography and computed tomography enterography, greater agreement was observed in detection of lumen reduction/dilatation (C = 96%). K showed considerable agreement in detection of mesenteric lymph nodes, fistulas, mural inflammation and thickening. The sensitivity, specificity, PPV and NPV were respectively set at 94.12% (95% CI 71.31-99.85), 50% (95% CI 6.76-93.24), 88.89% (95% CI 65.29-98.62) and 66.67% (95% CI 9.43-99.16) for CTE and 90.62% (95% CI 80.70-96.48), 33.33% (95% CI 4.33-77.72), 93.55% (95% CI 84.30-98.21) and 25% (95% CI 3.19-65.09) for MRIE. Conclusions: Although computed tomography enterography presents better sensitivity and specificity than magnetic resonance imaging enterography, both present high agreement values in detection of characteristic Crohn's disease findings, therefore the selection of the best test to monitor Crohn's disease should take into account aspects such as age, tolerability, disease phenotype and resources availability.